Significance of Brettanomyces and Dekkera during Winemaking: A Synoptic Review - Oelofse, A.; Pretorius, I.S.; du Toit, M. (South African Journal of Enology and Viticulture, 2016)
Wine comprises a complex microbial ecology of opportunistic microorganisms, some of which could potentially induce spoilage and result in consequent economic losses under uncontrolled conditions. Yeasts of the genus Brettanomyces, or its teleomorph Dekkera, have been indicated to affect the chemical composition of the must and wine by producing various metabolites that are detrimental to the organoleptic properties of the final product. These yeasts can persist throughout the harsh winemaking process and have in recent years become a major oenological concern worldwide. This literature review summarises the main research focus areas on yeasts of the genera Brettanomyces and Dekkera in wine. Specific attention is given to the spoilage compounds produced, the methods of detection and isolation from the winemaking environment and the factors for controlling and managing Brettanomyces spoilage.